A influência da adoção de tecnologias de meios de pagamento na satisfação do consumidor: um estudo com frequentadores de restaurante - FURTADO, Nilton Gomes (2017)
Aiming to investigate the relationship between consumers’ perceptions on use of payment technologies, this study consists of four specific objectives: 1) to identify the customers’ perceptions around payment technology in food and beverages industry; 2) analyze satisfaction level and its influence on consumer loyalty in the food and beverage industry; 3) identify critical success factors in customer-driven payment technologies deploying; and 4) relate the perceptions of payment technologies’ use to customer satisfaction. The mobile technology for payment topic is new in Brazil, despite the high diffusion of several kinds of mobile devices, beyond smartphones, such as watches and cards with NFC technology (Near Field Communication). Observing this phenomenon, in the initial stage of implementation in the food and beverage industry, the present study sought to describe the state of the art and articulate experiences in the literature from inside and outside the country. A survey had been held seeking to understand this global phenomenon and the impact of technology application in food and beverage industry in Brazil on costumer satisfaction; in which 950 respondents were inquired, 738 answered the questionnaire in full (77.68% of questionnaires), the respondents' average age is 35 years, and reached 26 states of the federation, having a significant sample in terms of population. Based on those answers, we seek to confirm or refute, through statistical analysis, the following hypotheses: H1 - Restaurant costumers' prefer establishments that adopt mobile payment technology in their service experience, H2 - Costumers perceive a better level of service, information and entertainment in service experience in restaurants that adopt mobile payment technology, H3 - The use of payment technologies acceptance can vary depending on its profile of the costumer, H4 - The use of payment technologies positively influences the perception of the costumers on satisfaction, convenience, exploration, precision and speed of delivery, H5: The use of payment technology negatively influences costumers' perception on need for human interaction in restaurants, H6 - When customers rely on payment technologies, the need for human interaction is decreased. We analyzed and categorized the collected data among factors that affect the perception and satisfaction of using mobile payment technologies in restaurants, and the quantitative study also allowed to understand which factors have the major impact on the perception and use of mobile payment technologies, identifying a set of relevant factors, as well as finding the advantages and disadvantages expected by costumers in the use of mobile payment technologies.